Diseño de un convertidor bidireccional y aislado AC/DC trifásico de una sola etapa de conversión tipo DABRS para aplicaciones de electromovilidad - Chavez Orihuela, Daniel (2025)
Electromobility is emerging as a key solution to address global environmental and energy challenges, driving a transition towards more sustainable transportation. In this context, electric vehicle chargers play a crucial role, with the electronic converter responsible for the interaction between the electrical grid and the battery. Traditionally, two-stage converters have been used, which present several disadvantages, such as low efficiency, bulkiness, heat dissipation issues, and limitations in reactive power injection, tolerance to imbalances, and bidirectionality. This thesis focuses on the development of a modulation and control strategy for a single-stage four active bridge resonant series (QABRS) converter, which offers significant benefits in terms of reduced size, higher efficiency, and durability compared to two-stage converters. The proposed modulation regulates the grid voltages using the duty ratio (DR), while the battery voltage is adjusted through a phase shift (PS) combined with DR. The DR for the battery is used exclusively for reactive power injection. Additionally, the DR angles in the grid control the sinusoidal shape of the grid currents through proportional-integral-resonant (PIR) controllers connected in cascade to a second-order low-pass filter and an active damping. Experimental results from a 1.5 kW prototype demonstrate a high efficiency of 96.4%, as well as bidirectional active and reactive power transfer capability, with a THD of 1.1%. These findings highlight that the proposed single-stage QABRS converter is an ideal alternative for bidirectional electric vehicle chargers (BEVC), underscoring its potential to enhance the performance and sustainability of electric vehicle charging systems.